FAKTOR-FAKTOR YANG MEMPENGARUHI KESIAPAN DAN PENERIMAAN TEKNOLOGI PADA SISTEM UJIAN ONLINE - Popon Handayani (Paradigma, 2013)
Online Examination System is highly prevalent among all education. One of the private collegesthat participate realize is STMIK NUSA MANDIRI. Implemented in reaction to the self-users, inthe form of acceptance or rejection. Acceptance of a technology is strongly influenced by thereadiness of the users of these technologies, it has been demonstrated empirically by Walczuch etal (2007). Adapting from these studies and research supporting the study entitled "Study ofPreparedness and Acceptance Testing System Technology Online: A Case Study STMIK NusaMandiri" aims to examine whether students in STMIK Nusa Mandiri Jakarta already has thereadiness and receive technologies on a system put in place. The model used to describe therelationship of the factors that affect the readiness and use Google Docs app is ReadnessTechnology Index (TRI) in the Technology Acceptance Model (TAM) by using the research methodof Structural Equation Modeling (SEM) on software analisys of Moment Structure (AMOS)version 21.0.Keywords: TRI, TAM, Online Examination System, SEM, dan AMOS